Keggin-Type Heteropolyacid for Ring-Opening Polymerization of Cyclohexene Oxide: Molecular Weight Control - Ahmed Aouissi; Zeid Abdullah Al-Othman; Abdurrahman Salhabi (International Journal of Polymer Science)
Polymerization of 1,2-cyclohexene oxide (CHO) in dichloromethane was catalyzed by 12-tungstophosphoric acid (H3PW12O40·13H2O) as a super solid acid. The effect of polymerization parameters such as reaction time, temperature, and catalyst amount was investigated. The effect of acetic anhydride as a ring-opening agent was also investigated. The resulting poly(1,2-cyclohexene oxide) (PCHO) was characterized by Fourier transform infrared (FTIR), nuclear magnetic resonance spectroscopy (1HNMR), gel-permeation chromatography (GPC), and differential scanning calorimetry (DSC). It has been found that the PCHO prepared over H3PW12O40·13H2O has a stereoregularity higher than that prepared over clay and Aluminium alkoxide catalysts. The Tg value obtained is due to the microstructure but not to molecular weight. The yield and the molecular weight of the polymer depend strongly on the reaction conditions. Molecular weights can be readily controlled by changing reaction temperature, reaction time, and catalyst amount. Contrary to most polymerization reactions, the molecular weight increases with the temperature increase. Addition of acetic anhydride to the reaction medium increased the yield threefold.